Paired phase II trials evaluating cetuximab and radiotherapy for low risk HPV associated oropharyngeal cancer and locoregionally advanced squamous cell carcinoma of the head and neck in patients not eligible for cisplatin. Issue 8 (27th January 2020) - Swiecicki, Paul L.; Li, Pin; Bellile, Emily; Stucken, Chaz; Malloy, Kelly; Shuman, Andrew; Spector, Matthew E.; Chinn, Steven; Casper, Keith; McLean, Scott; Moyer, Jeffery; Chepeha, Douglas; et al.
Abstract: Background: Alternative therapeutic strategies are needed for localized oropharyngeal carcinoma. Cetuximab represents a potential option for those ineligible for cisplatin or, until recently, an agent for de‐escalation in low risk HPV+ oropharyngeal carcinoma (OPSCC). Our objective was to define the toxicity and efficacy of cetuximab‐radiotherapy. Methods: We conducted paired phase II trials evaluating cetuximab‐radiotherapy in two cohorts (a) low risk HPV+ OPSCC and (b) cisplatin ineligible. The mean follow‐up was 48 months. Results: Forty‐two patients were enrolled in cohort A with a 2‐year disease free survival (DFS) of 81%. Twenty‐one patients were enrolled in cohort B prior to closure due to adverse outcomes with a 2‐year DFS of 37%. Severe toxicities were seen in 60% of patients, 30% required enteral nutrition. Conclusion: Among cisplatin ineligible patients, cetuximab treatment engendered poor outcomes. Rates of severe toxicities were on par with platinum‐based regimens suggesting that cetuximab is not a benign treatment.